2020
DOI: 10.1002/ijgo.13094
|View full text |Cite
|
Sign up to set email alerts
|

Spot urine protein‐to‐creatinine ratio as a diagnostic test in pre‐eclampsia: A gold standard?

Abstract: Objective To determine the diagnostic accuracy and optimal threshold of the spot protein‐to‐creatinine ratio (PCR) compared to the gold standard, 24‐hour proteinuria (24HP) in patients with suspected pre‐eclampsia. Methods A prospective observational study was performed from June 2015 to May 2017 consisting of patients hospitalized for suspected pre‐eclampsia in a tertiary care referral center. To compare the two diagnostic tests, a spot urine sample was obtained to perform the PCR before starting the collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Dong et al revealed that proteinuria in patients with pre-eclampsia is closely related to disease severity [ 27 ]. PCR is a simple, inexpensive and easily accessible method to assess the magnitude of proteinuria and the function of glomerular cell [ 16 , 28 , 29 ]. In this study, CT was significantly increased with elevated PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al revealed that proteinuria in patients with pre-eclampsia is closely related to disease severity [ 27 ]. PCR is a simple, inexpensive and easily accessible method to assess the magnitude of proteinuria and the function of glomerular cell [ 16 , 28 , 29 ]. In this study, CT was significantly increased with elevated PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In study by Berthet et al, the area under the curve for spot PCR was 0.92, with higher accuracy in diagnosing the proteinuria and thus pre-eclampsia. 11 In a study, Sharma et al documented the AUC for PCR was 0.793, p<0.05. 7 On assessment of diagnostic accuracy in term of sensitivity, specificity, PPV, NPV and accuracy of each method compared with the 24-hour urinary total protein estimation.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, 24‐hour urine collection was considered the appropriate comparator for proteinuria quantification 8 but it has since been replaced in the UK with laboratory PCR testing. Recommended by NICE, 2 PCR testing is more accurate, 15 less time‐consuming and more convenient for women than 24‐hour urine collection 19,20 . The majority of studies examining point‐of‐care testing for proteinuria have used 24‐hour urine collection as a primary reference test, and those using PCR have not reported on self‐testing 21…”
Section: Discussionmentioning
confidence: 99%
“…Recommended by NICE, 2 PCR testing is more accurate, 15 less time-consuming and more convenient for women than 24-hour urine collection. 19,20 The majority of studies examining point-of-care testing for proteinuria have used 24-hour urine collection as a primary reference test, and those using PCR have not reported on self-testing. 21 A limitation to the study was that pregnant women performed a one-off test in a clinic environment.…”
Section: Strengths and Limitationsmentioning
confidence: 99%